Antimicrobial Fatty Acids from Green Alga Ulva rigida (Chlorophyta) - Ismail, Amel (Biomed Res Int, 2018)
This study deals with the antimicrobial potential assessment of Ulva rigida, in regard to collection period and sampling site. Besides, we assess the chemical composition of bioactive compounds. For this purpose, Ulva rigida was seasonally collected from two northern sites in Tunisia, Cap Zebib rocky shore (CZ) and Ghar El Melh lagoon (GEM). Crude organic extracts were prepared using dichloromethane and dichloromethane/methanol and tested against 19 indicator microorganisms using the disk diffusion method and microdilution technique to determine the minimum inhibitory concentration (MIC). Silica gel column and thin layer chromatography were used for purification of active compounds. Nuclear magnetic resonance (NMR) and gas chromatography were used for compounds identification. Samples of Ulva rigida collected from the two sites have uniform antimicrobial activity throughout the year. Algae collected from the lagoon showed the largest spectrum of activity and were used for subsequent analysis. Bioguided purification of extracts from Ulva rigida, collected at GEM, leads to 16 active fractions with antibacterial effect mainly against Staphylococcus aureus ATCC 25923 and Enterococcus faecalis ATCC 29212. These fractions were identified as fatty acids, mainly oleic (C18: 1 w9), linoleic (C18: 2 w6), palmitic (C16: 0), and stearic (C14: 0). MICs values ranged from 10 to 250 μg/ml.